Up-conversion luminescence and Judd–Ofelt analysis of Nd2O3-doped yttria stabilized zirconia single crystals. Issue 34 (27th July 2022) - Zhang, Peng; Wu, Wenxia; Wu, Limin; Wang, Yazhao; Ta, Shengdi; Cheng, Zeyu; Xu, Shoulei; Goodman, Bernard Albert; Deng, Wen
Abstract : The growth, structure and optical properties of (ZrO2 )92 (Y2 O3 )8− x (Nd2 O3 ) x single crystals were reported. The maximum intensity of the emission spectra was with 0.75 mol% Nd2 O3, indicating this sample has potential for near-UV up-conversion luminescence and laser output. Abstract : Transparent single crystals of (ZrO2 )92 (Y2 O3 )8− x (Nd2 O3 ) x ( x = 0.30, 0.50, 0.75, 1.00, 1.25, 1.50) were prepared by the optical floating zone method, and shown by XRD to have a cubic phase structure. Nd 3+ entered into the crystal structure during crystal growth, and the lattice parameters and cell volume increased with increasing Nd2 O3 concentration as Nd 3+ replaced the smaller Y 3+ . A series of absorption peaks involving transitions from the Nd 3+ ground state ( 4 I9/2 ) were observed in the UV-vis-NIR absorption spectra. Under excitation with yellow light at 589 nm, up-conversion luminescence spectra showed three distinct emission peaks, corresponding to the 4 D5/2 → 4 I9/2 (334 nm), 4 D3/2 → 4 I9/2 (363 nm) and 2 P1/2 → 4 I9/2 (442 nm) transitions. The maximum intensity of the emission spectra was with 0.75 mol% Nd2 O3, and higher concentrations resulted in quenching through electric dipole–quadrupole interactions. From analysis of the absorption and emission spectra using the Judd–Ofelt theory, values for the strength parameters Ω t ( t = 2, 4, 6) and radiative transition properties were obtained for the (ZrO2 )92 (Y2 O3 )7.25 (Nd2 O3 )0.75 single crystal. These showed Ω 4 > Ω 2 > Ω 6, with the large Ω 2 value indicating a highly covalent interaction and asymmetric local environment for Nd 3+ . The spectroscopic quality factor ( χ ) and radiative properties, such as the transition probability, radiation lifetime and branching ratio, indicate that this sample is a potential material for near-UV up-conversion luminescence and laser output.